Experimental study on the accuracy of non-invasive temperature measurement by magnetic resonance in microwave ablation. - Guo, Rui; Wang, Xianjian; Liu, Jie; Chen, Jin; Chen, Jian; Lin, Qingfeng; Yan, Yuan; Liang, Ping; Lin, Zhengyu (Journal of Cancer Research & Therapeutics, 2022)
Aims: This study aimed to explore the accuracy of non-invasive temperature measurement based on proton resonance frequency (PRF) phase subtraction in microwave ablation (MWA).Methods and Material: The signal change of the agar phantom during the ablation process was monitored by the gradient echo sequence under 1.5 T superconducting magnetic resonance imagining (MRI), and the temperature change was converted by the phase subtraction method of the PRF, which was compared with the temperature measured using an optical fiber.Statistical Analysis Used: SPSS software version 22.0 was used for data processing, and the independent sample t-test was used for comparative analysis. P < 0.05 indicated statistical significance.Results: The maximum error between the MRI temperature measurement and the standard value was 3.61°C, whereas the minimum and average errors were 0.01°C and 1.19°C ± 0.78°C, respectively.Conclusions: The temperature measurement technology, which is based on the PRF phase method, has good accuracy in MRI-guided MWA.